Gender dominant interaction design in the Legend of Zelda: Echoes of Wisdom - Lovell, Carrie, author; Amidon, Timothy R., advisor; Szymanski, Erika, committee member; Arthur, Tori, committee member (Colorado State University. Libraries, 2025)
Interaction Design (IxD) implements rhetorical concerns in the design of digital interfaces, usually used to consider how websites are designed to improve user experience. This thesis applies this concept to the design of interactions in video games, specifically concerning how IxD is engineered to convey gendered experiences. The work with IxD done in this thesis uses Sano-Franchini's concept of Feminist Interaction Design (F-IxD) as a starting point for conceptualizing other ways in which gender impacts IxD and user experience. Specifically, the research question addresses how game design imposes gender and gender ideologies through various interactions and how that impacts player experience through The Legend of Zelda: Echoes of Wisdom (2024). This research was conducted through an exploratory case study, using qualitative coding analysis to identify how the larger community experiences the game within the r/echoesofwisdom subreddit, and using close reading analysis to identify how my positionality impacts my gendered experience through gameplay video capture and field notes. Through this research, it was found that The Legend of Zelda: Echoes of Wisdom demonstrates shifts in game design that appear to be connected to the implementation of a female protagonist. This thesis (1) problematizes existing research, illustrating that not only is the field viewing gender in video games at a visual surface level, but would also benefit from specific definitions of key terms, such as passive gameplay, and (2) proposes the implementation of Costanza-Chock's existing design justice principles to mitigate existing and future gendered IxD paradigms.
Keywords: game design; gameplay; interaction design; game rhetoric; feminist; gender